2008
DOI: 10.1016/j.amjcard.2008.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Volume Characteristics in Anemic Patients With Low Versus Preserved Left Ventricular Ejection Fractions

Abstract: Anemia is a significant co-morbidity in patients with heart failure (HF) irrespective of EF (EF) and is routinely quantified by hemoglobin concentration. Hemodilution as a cause of anemia has been described in systolic HF. This study aims to further investigate the effects of plasma volume in HF patients by 1) assessing prevalence of dilutional anemia in patients with anemia and a preserved EF and 2) exploring the relation between hemoglobin and red cell volume in these patients. Forty-six anemic patients (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 27 publications
6
59
0
2
Order By: Relevance
“…Its prevalence is similar to that of CKD, diabetes, and COPD 229, 230, 231. Anemia is mostly prevalent in elderly women with advanced HFpEF, CKD, and diabetes 232, 233, 234.…”
Section: Comorbid Conditionsmentioning
confidence: 87%
“…Its prevalence is similar to that of CKD, diabetes, and COPD 229, 230, 231. Anemia is mostly prevalent in elderly women with advanced HFpEF, CKD, and diabetes 232, 233, 234.…”
Section: Comorbid Conditionsmentioning
confidence: 87%
“…Abramov et al 9 reported that patients with heart failure with preserved ejection fraction (HFpEF) had a lower total blood volume (ie, the intravascular volume) than those with heart failure with reduced ejection fraction (HFrEF). Similarly, Schwartzenberg et al 10 reported a greater stroke volume reduction in HFpEF than in HFrEF after vasodilation treatment, indicating the presence of occult intravascular hypovolemia in HFpEF.…”
Section: Clinical Perspective On P 532mentioning
confidence: 99%
“…Second, we estimated the intravascular volume using the ideal body weight method. 28 Although this method was validated in both healthy volunteers and in patients with heart failure, 9 changes in the ratio of intravascular volume to body weight, which are likely to occur during AHF treatment, may modify the results. Therefore, in future studies, PV needs to be evaluated more precisely using scintigraphy or bioimpedance analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a primary pathophysiologic derangement of HF is the expansion of the PV and, therefore, it becomes difficult to accurately differentiate true anemia from dilution-related anemia or even the presence of excess RBCM (polycythemia) based on peripheral hemoglobin or hematocrit measurements alone. [22][23][24] Although the importance of a low hemoglobin and its causes in chronic HF should not be underestimated in terms of outcome implications, 25 the concept of pseudoanemia secondary to PV excess and even with RBCM polycythemia has been underrecognized. As a result, in the clinical setting of volume overload chronic HF, the complex of true anemia, pseudoanemia, and RBCM polycythemia with PV expansion and the relation to peripheral venous hemoglobin values has gone, with a few exceptions, 12,26 largely unreported and with it the implications for volume management.…”
Section: Millermentioning
confidence: 99%